Animorphs. 4, The message - Grine, Chris; Applegate, Katherine; Grant, Michael, 1954- (Animorphs (Graphic novel), 2023)
It begins with the dreams. Cassie has been having strange nightmares of a voice calling to her from deep beneath the ocean. They're unsettling, but it isn't until Cassie discovers Tobias has been having dreams too, the exact same dreams, of a voice pleading for help -- that she decides it's time to start listening. When pieces of debris wash up on shore, marked with alien writing, the team realises they may still have allies in the fight for Earth, allies who are trying to make contact. Now they just have to reach them, before time runs out.